Thermoresponsive Semi-IPN Hydrogel Microfibers from Continuous Fluidic Processing with High Elasticity and Fast Actuation - Liu, Yan; Zhang, Kaihuan; Ma, Jinghong; Vancso, G. Julius (ACS applied materials & interfaces, 2017)
Hydrogels with rapid and strong response to external stimuli and possessing high elasticity and strength have been considered as platform materials for numerous applications, e.g., in biomaterials engineering. Thermoresponsive hydrogels based on semi-interpenetrating polymer networks (semi-IPN) featuring N-isopropylacrylamide with copolymers of poly(N-isopropylacrylamide-co-hydroxyethyl methacrylate) p(NIPAM-HEMA) chains are prepared and described. The copolymer was characterized by FTIR, NMR, and GPC. The semi-IPN structured hydrogel and its responsive properties were evaluated by dynamic mechanical measurements, SEM, DSC, equilibrium swelling ratio, and dynamic deswelling tests. The results illustrate that the semi-IPN structured hydrogels possess rapid response and high elasticity compared to conventional pNIPAM hydrogels. By using a microfluidic device with double coaxial laminar flow, we succeeded in fabricating temperature responsive (“smart”) hydrogel microfibers with core–shell structures that exhibit typical diameters on the order of 100 μm. The diameter of the fibers can be tuned by changing the flow conditions. Such hydrogel fibers can be used to fabricate “smart” devices, and the core layer can be potentially loaded with cargos to incorporate biological function in the constructs. The platforms obtained by this approach hold promise as artificial “muscles”, and also “smart” hydrogel carriers providing a unique biophysical and bioactive environment for regenerative medicine and tissue engineering.